Ground Movement Tracking System for Airside Operations using Global Navigation Satellite System (GNSS) and Long Range (LoRa) Communication - Cokorda Dwija Wisnuardana; Johan Wahyudi; Muhammad Arif Sulaiman (Aviation Electronics, Information Technology, Telecommunications, Electricals, and Controls (AVITEC), 2026)
Accurate monitoring of ground vehicle and aircraft movement in the airport airside is essential to reduce the risk of incidents caused by limited coordination between controllers, pilots, and ground operators. This study proposes the design of a ground movement tracking system for airside operations, utilizing a Global Navigation Satellite System (GNSS) module (Matek M10Q-5883) and a Long Range (LoRa) communication module (LILYGO ESP32), integrated with a web dashboard for real-time visualization. The system was developed using the Waterfall methodology, covering requirement analysis, system design, hardware and software implementation, and performance testing in simulated airside conditions. Experimental results show that the system achieved an average coordinate deviation of only 0.000017º equivalent to about 1.7 meters  compared to a reference device, and maintained reliable data transmission up to 1.4 km under line-of-sight conditions. These findings demonstrate that the proposed system provides accurate and stable monitoring of ground movements, offering a cost-efficient and weather-independent alternative to GSM-based solutions. In addition, by optimizing LoRa parameters, the system successfully extended its communication range beyond the ~1 km typically reported in related studies, highlighting its novelty and contribution to enhanced safety in airport operations.